Effects of cirrus heterogeneity on lidar CALIOP/CALIPSO data. (November 2017) - Alkasem, A.; Szczap, F.; Cornet, C.; Shcherbakov, V.; Gour, Y.; Jourdan, O.; Labonnote, L.C.; Mioche, G.
Highlights: Heterogeneous cirrus clouds are generated. Lidar signals are simulated using a Monte-Carlo code. Effects on CALIOP lidar measured data are evaluated. Importance of horizontal photon transport is underscored. Abstract: The goal of this work is to evaluate the effects of cirrus heterogeneity on characteristics that are directly measured by the CALIOP/CALIPSO lidar, i.e. attenuated backscatter coefficient and depolarization ratio. This assessment was done using the 3D Monte Carlo simulator of Polarized Lidar signals (3DMcPOLID) together with the high-resolution 3D cloud fields-generator 3DCLOUD_V2. The evaluation is based on random sampling and on comparison between mean profiles of 3D clouds and of plane-parallel equivalent 1D clouds. Mean profiles of the apparent attenuated backscatter as well as of the integrated apparent backscatter are statistically equal when a cirrus cloud field is probed with the 325 m resolution. To the contrary, the difference between profiles is statistically significant in the case of the 1 km resolution. Profiles of the volume depolarization ratio are statistically different for both cases of the horizontal resolution. The total bias of CALIOP/CALIPSO lidar data is mainly due to the plane parallel bias and multiple scattering, i.e., horizontal photon transport.